Precision Regulation Approach: A COVID-19 Triggered Regulatory Drive in South Korea - Lee, Sora; Kang, Woojin (Frontiers in Public Health, 2021)
COVID-19 has triggered various changes in our everyday lives and how we conceptualize the functions of governments. Some areas require stricter forms of regulation while others call for deregulation. The challenge for the regulatory authorities is to manage these potentially conflicting demands in regulation and define coherently their overall regulatory rationale. The precision regulation approach can be a helpful approach. It is defined here as a streamlined approach to regulation to deliver the right methods of regulation for the right group of people at the right time. This problem-solving innovation in regulation triggered by the recent epidemiologic crisis in South Korea demonstrates the emergence of the precision regulation approach. South Korea has implemented streamlined fast-track services for the biotechnology industry to produce test kits swiftly. This article expands the definition of precision regulation from AI regulation literature, and positions the term as a new regulatory rationale, not as a regulatory tool, using the case study from South Korea.